The Religious Land Use and Institutionalized Persons Act and Limits of Religious Advisors Within the Execution Chamber - Sarah Zanola (Washington University Journal of Law and Policy, 2023)
A prisoner’s right to free exercise of religion within the execution chamber has been considered across time through both legislative and judicial action. The Supreme Court will take up the issue again in Ramirez v. Collier. Ramirez, a prisoner awaiting execution, argues that his execution must be stayed because Texas’ policy of prohibiting religious advisors from touching prisoners in their final moments or speaking aloud in the execution chamber violates the Religious Land Use and Institutionalized Persons Act (RLUIPA) as well as the First Amendment right to freedom of religion. This Note provides a historical analysis of the Supreme Court’s prior interpretations of cases concerning RLUIPA, including the Court’s most recent decision in Dunn v. Smith. Moreover, the Author argues that Texas’ current policies concerning religious advisors in execution chambers violate RLUIPA and thus, Ramirez’s execution must be stayed. Ultimately, this Note argues that while Texas does have a compelling state interest in maintaining the security of prisons, the prohibitions placed on the conduct of religious leaders in execution chambers is not the least restrictive means of achieving that interest and as a result it constitutes a substantial burden on inmates’ ability to practice sincerely held religious beliefs.
Keywords: Prison Rights; Execution; Religion; RLUIPA; First Amendment